2018
DOI: 10.1002/smtd.201800291
|View full text |Cite
|
Sign up to set email alerts
|

Single or Double: Which Is the Altar of Atomic Catalysts for Nitrogen Reduction Reaction?

Abstract: Converting N2 to NH3 is an extremely valuable process but a long‐standing challenge in chemistry. The crux is the choice of catalysts, where single atomic catalysts (SAC) are always pursued as the altar of atomic catalysts. In this paper, double atomic catalysts (DAC) of TM2‐C2N with SAC of TM‐C2N (TM = Cr, Mn, Fe, Co, and Ni) for nitrogen reduction reaction (NRR) are systematically compared. Unexpectedly, TM2‐C2N are more suitable than TM‐C2N as catalysts for NRR. Moreover, the Mn2‐C2N endows the highest cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
184
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(189 citation statements)
references
References 47 publications
5
184
0
Order By: Relevance
“…Experimentally Yan et al synthesized the stable platinum dimers (but dominantly in the oxidized form of Pt 2 O x without PtPt bond) on graphene using atomic layer deposition, and demonstrated that Pt 2 dimers exhibit higher activity toward hydrolytic dehydrogenation of ammonia borane than that of graphene supported Pt 1 single atoms and nanoparticles . Theoretically, Luo et al predicted that the Pd dimer embedded in graphene can effectively and selectively catalyze formic acid dehydrogenation; Sun and co‐workers proposed that Cu dimer on graphene or Mn dimer on a phthalocyanine sheet exhibit higher catalytic activity for CO 2 reduction; Compared with their single‐atom counterparts, several double transition metal (TM) atoms supported by 2D crystal C 2 N were predicted to have better catalytic performance for oxygen reduction reaction and CO oxidation than their single‐atom counterparts; Several other transition metal dimers anchored on C 2 N monolayers were also expected to exhibit high activity for some important chemical reactions, e.g., carbon dioxide electrochemical reduction (Cu 2 @C 2 N), hydrogen evolution reaction (Co 2 @C 2 N, Ni 2 @C 2 N, Cu 2 @C 2 N, Ru 2 @C 2 N), and nitrogen fixation (Mo 2 @C 2 N, Mn 2 @C 2 N) …”
Section: Introductionmentioning
confidence: 99%
“…Experimentally Yan et al synthesized the stable platinum dimers (but dominantly in the oxidized form of Pt 2 O x without PtPt bond) on graphene using atomic layer deposition, and demonstrated that Pt 2 dimers exhibit higher activity toward hydrolytic dehydrogenation of ammonia borane than that of graphene supported Pt 1 single atoms and nanoparticles . Theoretically, Luo et al predicted that the Pd dimer embedded in graphene can effectively and selectively catalyze formic acid dehydrogenation; Sun and co‐workers proposed that Cu dimer on graphene or Mn dimer on a phthalocyanine sheet exhibit higher catalytic activity for CO 2 reduction; Compared with their single‐atom counterparts, several double transition metal (TM) atoms supported by 2D crystal C 2 N were predicted to have better catalytic performance for oxygen reduction reaction and CO oxidation than their single‐atom counterparts; Several other transition metal dimers anchored on C 2 N monolayers were also expected to exhibit high activity for some important chemical reactions, e.g., carbon dioxide electrochemical reduction (Cu 2 @C 2 N), hydrogen evolution reaction (Co 2 @C 2 N, Ni 2 @C 2 N, Cu 2 @C 2 N, Ru 2 @C 2 N), and nitrogen fixation (Mo 2 @C 2 N, Mn 2 @C 2 N) …”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from the high reactivity of Ru and monoatomic dispersion, the Ru SAs /N−C achieved a high Faradaic efficiency of 29.6 %, and the yield rate reached 120.9 μg h −1 mg −1 of NH 3 at −0.2 V (RHE), which is higher than that of Ru NPs/N−C (Figure ) . This work not only exceeded the results reported at the time but also became a guide for the study of the uniform distribution of single atomic catalysts to improve the applicability of electrochemical nitrogen fixation …”
Section: Nrr Catalystsmentioning
confidence: 51%
“…[24a] This work not only exceeded the results reported at the time but also became a guide for the study of the uniform distribution of single atomic catalysts to improve the applicability of electrochemical nitrogen fixation. [12,33]…”
Section: Noble-metal Catalystsmentioning
confidence: 99%
“…More recently, double‐atom catalysts have been proposed for enhanced NRR activity over SACs due to the synergetic effects between adjacent active centers, as well as higher metal atom loading and more flexible active sites . For instance, single or double TM atoms can be anchored in the uniform big holes of monolayer C 2 N, which are stabilized by the abundant and uniform pyridine‐like N atoms ( Figure a–c) .…”
Section: Nitrogen Fixation At Atomic‐scale Active Sitesmentioning
confidence: 99%